The Future of Personalized Medicine in Space: From Observations to Countermeasures - Pavez Loriè, Elizabeth; Baatout, Sarah; Choukér, Alexander; Buchheim, Judith-Irina; Baselet, Bjorn; Dello Russo, Cinzia; Wotring, Virginia; Monici, Monica; Morbidelli, Lucia; Gagliardi, Dimitri; Stingl, Julia Caroline; Surdo, Leonardo; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
The aim of personalized medicine is to move away from a ‘one-size fits all approach’ and improve patient health by individualization to achieve the best outcomes in disease prevention, diagnosis and treatment. Technological advances in sequencing technologies, improved knowledge of ‘-omics’, integration with bioinformatics and new in vitro testing formats, have enabled personalized medicine to become a reality. Individual variation in response to environmental factors can affect susceptibility to disease and response to treatments. Space travel exposes humans to environmental stressors that lead to physiological adaptations, from altered cell behavior to abnormal tissue responses, including immune system impairment. In the context of human space flight research, human health studies have shown a significant inter-individual variability in response to space analogue conditions. A substantial degree of variability has been noticed in response to medications (from both an efficacy and toxicity perspective) as well as in susceptibility to damage from radiation exposure and in physiological changes such as loss of bone mineral density and muscle mass in response to deconditioning. At present, personalized medicine for astronauts is limited. With the advent of longer duration missions beyond low Earth orbit, it is imperative that space agencies adopt a personalized strategy for each astronaut, starting from pre-emptive personalized pre-clinical approaches through to individualized countermeasures to minimize harmful physiological changes and find targeted treatment for disease. Advances in space medicine can also be translated to terrestrial applications, and vice versa. This review places the astronaut at the center of personalized medicine and will review existing evidence and future preclinical tools as well as clinical, ethical and legal considerations for future Space travel.